KONSELOR SEKOLAH ABAD 21: TANTANGAN DAN PELUANG - Dini Rakhmawati (JURNAL KONSELING GUSJIGANG, 2017)
Technological developments, especially in the field of information and communication in the 21st century has a significant influence for guidance and counseling services in Indonesia. Currently we are in a competitive era of increasingly tight, it takes preparation to establish a human resources are superior. School counselors are the front-line mental health professionals to students and families, this is a tough challenge given the student problems of today's increasingly complex. An important component in turning challenges into opportunities is to keep practicing to develop themselves, learn new skills that match the needs of the students of today. The skills most needed now is a cultural competency skills and mastery of technology.